2005
DOI: 10.1002/adma.200500747
|View full text |Cite
|
Sign up to set email alerts
|

Stable Amorphous CaCO3 Microparticles with Hollow Spherical Superstructures Stabilized by Phytic Acid

Abstract: Amorphous CaCO3 (ACC) is stabilized by the presence of phytic acid, a natural inositol hexakisphosphate (IP6). Micrometer‐sized hollow spheres of ACC have been obtained (see Figure). The spheres are stable for at least three months in solution, which is equivalent to that described for more complex special biopolymers in biomineralization processes, and by far exceeds the previously known stability of ACC prepared in the presence of synthetic molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
144
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(151 citation statements)
references
References 44 publications
6
144
0
1
Order By: Relevance
“…This is because a variety of intermediates of the PAA-Ca 2+ -H 2 O complex coexist in the earlier stage of complexation; that is, the coordination of Ca 2+ ions with PAA is more random earlier in the reaction. Phytic acid is another effective inhibitor of the crystallization of ACC nanospheres fabricated using a gas-diffusion method, as described by Xu et al [43]. They also found that hydrated ACC can form on the exterior of anhydrous ACC and then grow at the expense of the dissolving internal anhydrous ACC particles, producing a hollow nanostructure.…”
Section: Morphologies Of Amorphous Nanomaterials Spheresmentioning
confidence: 92%
See 2 more Smart Citations
“…This is because a variety of intermediates of the PAA-Ca 2+ -H 2 O complex coexist in the earlier stage of complexation; that is, the coordination of Ca 2+ ions with PAA is more random earlier in the reaction. Phytic acid is another effective inhibitor of the crystallization of ACC nanospheres fabricated using a gas-diffusion method, as described by Xu et al [43]. They also found that hydrated ACC can form on the exterior of anhydrous ACC and then grow at the expense of the dissolving internal anhydrous ACC particles, producing a hollow nanostructure.…”
Section: Morphologies Of Amorphous Nanomaterials Spheresmentioning
confidence: 92%
“…Spherical structure is also favorable in terms of surface energy. Nanospheres are the most reported shape of amorphous materials in the last decade (see Table 1), and they can be composed of calcium carbonate (CaCO 3 ) [43][44][45][46][47], silicon (Si) [48][49][50][51][52], metals or their compounds [53][54][55][56][57][58][59][60][61]. CaCO 3 is abundant in the natural world, and a typical model system used to mimic the mineralization process of biominerals [43].…”
Section: Morphologies Of Amorphous Nanomaterials Spheresmentioning
confidence: 99%
See 1 more Smart Citation
“…(6) Several techniques have been reported for the synthesis and stabilization of ACC, (4,7) but all known methods use either toxic materials or various organic polymers to stabilize ACC for more than 3 days. (7)(8)(9)(10)(11) To avoid use of such compounds, a novel method for synthetic production of stabilized ACC using phosphoaminoacids was developed recently (12) and was shown to stabilize ACC for more than 4 months under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…(10,13,14) In most cases, these organisms use calcium in the amorphous phase as a precursor for one of the crystalline phases. (15) In other instances, organisms construct specialized transient mineral storage sites composed of stabilized amorphous calcium carbonate embedded on an organic matrix comprising dense chitin fibers and proteins.…”
Section: Introductionmentioning
confidence: 99%